Pemanfaatan Buku Kesehatan Ibu dan Anak (KIA) oleh Ibu Hamil dalam Meningkatkan Pengetahuan dan Kepatuhan Pemeriksaan Kehamilan di Wilayah Kerja Puskesmas Medono Kota Pekalongan - Hilda Prajayanti; Swasti Artanti (LPPM Universitas Bhamada Slawi PSDKU D III Kebidanan Kampus Kota Pekalongan, 2025)
The Maternal and Child Health (MCH) Handbook is an essential communication and educational tool in maternal health services. It contains information on pregnancy, childbirth, postpartum care, and child development, and serves as a health record for both mother and child. However, in practice, the utilization of the MCH Handbook by pregnant women remains low and suboptimal. This issue can lead to limited maternal knowledge and irregular antenatal care (ANC) visits. This study aims to examine the relationship between the utilization of the MCH Handbook and the level of knowledge and compliance of pregnant women regarding antenatal care. A quantitative research method with a cross-sectional design was used. A total of 100 pregnant women visiting the X Public Health Center were selected through purposive sampling. Data were collected using a structured questionnaire and analyzed with Chi-Square and Pearson correlation tests. The results show that women who read the MCH Handbook thoroughly had the highest compliance with ANC visits (90%), compared to those who read partially (70%) or did not read at all (50%). A significant relationship was found between the level of MCH Handbook utilization and maternal compliance with ANC (p < 0.05). These findings indicate that the MCH Handbook can serve as an effective educational medium when used properly and supported by health workers.